Analisis efektivitas pelaksanaan pemungutan Bea Perolehan Hak atas Tanah dan Bangunan dan sosialisasi perpajakan terhadap penerimaan Bea Perolehan Hak atas Tanah dan Bangunan - Yohana Danut; Ary Yunita Anggraeni (University of Merdeka Malang, 2021)
This study aims to describe whether the tax collection and socialization system can streamline BPHTB revenue, to describe how big the impact of the tax collection system and tax socialization on BPHTB revenue, and also aims to describe whether BPHTB revenue has experienced a significant increase from the tax collection and socialization system. The research method used is a qualitative method by using data collection techniques through observation or observations, interviews and documentation. Observations were made, namely Observing and collecting data directly in the field to obtain data relating to the implementation of tax collection by the Tax bailiff at the Malang City Revenue Service office, then the author also conducted interviews with one of the related parties, namely Mr. Solikin as Deputy Head Regional Tax Division at the Malang City Regional Revenue Agency office. The results of the research that the author did show that the level of effectiveness of the implementation of tax collection and socialization on BPHTB revenues has been effective, this is evidenced by an increase in BPHTB revenues in 2017 the percentage of BPHTB receipts by 125% or categorized as very effective, in 2018 the percentage of 101% is also categorized as very effective, except that in 2019 it decreased by a percentage level of 74% due to delays in payment of BPHTB taxes at the Malang City Regional Revenue Agency. However, based on the average percentage from 2017 to 2019 the effectiveness of the implementation of BPHTB collection and tax socialization on BPHTB revenues is quite effective, with a percentage of 100%.